Heterologous expression and characterization of xylose-tolerant GH 43 family β-xylosidase/α-L-arabinofuranosidase from Limosilactobacillus fermentum and its application in xylan degradation - Vasquez, Robie; Song, Ji Hoon; Lee, Jae Seung; Kim, Sanghoon; Kang, Dae-Kyung (Frontiers in Bioengineering and Biotechnology, 2025)
The degradation of hemicellulose, including xylan, is an important industrial process as it provides cheap and sustainable source of economically valuable monosaccharides. β-xylosidases are key enzymes required for complete degradation of xylan and are used in the production of monosaccharides, such as xylose. In this study, we characterized a novel, xylose-tolerant β-xylosidase isolated from Limosilactobacillus fermentum SK152. Sequence analysis and protein structure prediction revealed that the putative β-xylosidase belongs to the glycoside hydrolase (GH) family 43 subfamily 11 and exhibits high homology with other characterised GH43 β-xylosidases from fungal and bacterial sources. The putative β-xylosidase was named LfXyl43. The catalytic residues of LfXyl43, which are highly conserved among GH 43 β-xylosidases, were predicted. To fully characterise LfXyl43, the gene encoding it was heterologously expressed in Escherichia coli. Biochemical characterisation revealed that the recombinant LfXyl43 (rLfXyl43) was active against artificial and natural substrates containing β-1,4-xylanopyranosyl residues, such as p-nitrophenyl-β-D-xylopyranoside (pNPX) and oNPX. Moreover, it demonstrated weak α-L-arabinofuranosidase activity. The optimal activity of rLfXyl43 was obtained at pH 7.0 at 35°C. rLfXyl43 could degrade xylo-oligosaccharides, such as xylobiose, xylotriose, and xylotetraose, and showed hydrolysing activity towards beechwood xylan. Moreover, rLfXyl43 demonstrated synergy with a commercial xylanase in degrading rye and wheat arabinoxylan. The activity of rLfXyl43 was not affected by the addition of metal ions, chemical reagents, or high concentrations of NaCl. Notably, rLfXyl43 exhibited tolerance to high xylose concentrations, with a Ki value of 100.1, comparable to that of other xylose-tolerant GH 43 β-xylosidases. To our knowledge, this is the first β-xylosidase identified from a lactic acid bacterium with high tolerance to salt and xylose. Overall, rLfXyl43 exhibits great potential as a novel β-xylosidase for use in the degradation of lignocellulosic material, especially xylan hemicellulose. Its high activity against xylo-oligosaccharides, mild catalytic conditions, and tolerance to high xylose concentrations makes it a suitable enzyme for industrial applications.